2020
DOI: 10.36401/jipo-20-10
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications of Chimeric Antigen Receptor T-Cell Therapy: The Cytokine Release Syndrome and Associated Arrhythmias

Abstract: In recent years, cancer treatment has evolved, and new therapies have been introduced with significant improvement in prognosis. The immunotherapies stand out owing to their efficacy and remission rate. Chimeric antigen receptor (CAR) T-cell therapy is a part of this new era of therapies. Chimeric antigen receptor T-cell therapy is a form of adoptive cellular therapy that uses a genetically encoded CAR in modified human T cells to target specific tumor antigens in a nonconventional, non-major histocompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…IL-6 is one of the driving pro-inflammatory cytokines that contributes to CRS and its pulmonary, cardiovascular, renal and neurologic complications [ 17 , 18 , 19 , 20 , 21 , 36 , 37 ]. Cytokine profiling in patients who developed CRS after APVO436 infusion indicated that the predominant cytokine in this inflammatory cytokine response was IL-6, which was in agreement with our current knowledge regarding CRS that occurs in the context of BiAb therapy [ 14 , 15 , 16 , 38 , 39 , 40 ]. Within 1–2 days following the first dose of APVO436, the mean serum IL-6 concentration was elevated 145-fold over the baseline (755 vs. 5.2) and at the end of one week it was still elevated 83-fold over the baseline.…”
Section: Discussionsupporting
confidence: 88%
“…IL-6 is one of the driving pro-inflammatory cytokines that contributes to CRS and its pulmonary, cardiovascular, renal and neurologic complications [ 17 , 18 , 19 , 20 , 21 , 36 , 37 ]. Cytokine profiling in patients who developed CRS after APVO436 infusion indicated that the predominant cytokine in this inflammatory cytokine response was IL-6, which was in agreement with our current knowledge regarding CRS that occurs in the context of BiAb therapy [ 14 , 15 , 16 , 38 , 39 , 40 ]. Within 1–2 days following the first dose of APVO436, the mean serum IL-6 concentration was elevated 145-fold over the baseline (755 vs. 5.2) and at the end of one week it was still elevated 83-fold over the baseline.…”
Section: Discussionsupporting
confidence: 88%
“…Chimeric Antigen Receptor T cell therapy (CAR-T), currently utilized in the treatment of R/R MM, can lead to direct and indirect cardiac toxicities, mainly through the associated cytokine release syndrome (CRS), where the increase in several inflammatory markers and cytokines can lead to hypotension, tachycardia/arrhythmias partly related to the activation of the sympathetic nervous system leading to cardiac stimulation, in addition to VD related to possible myocyte shortening and mitochondrial dysfunction [ 43 ]. No cardiac failure was reported with Idecabtagene vicleucel in the KarMMa trial [ 44 ].…”
Section: Other Therapies Including Elotuzumab Bispecific Agents and C...mentioning
confidence: 99%
“…The most common abnormalities found in these patients are asymptomatic prolonged QTc interval and atrial fibrillation. Hypotension has been reported in up to one-third of patients with CRS [75]. The other reported cardiac toxicities include an increase in serum troponins and a decrease in left ventricular systolic function.…”
Section: Anti-cd19 Car T-cells Cause B-cell Aplasia and Hypogammaglobmentioning
confidence: 99%
“…The other reported cardiac toxicities include an increase in serum troponins and a decrease in left ventricular systolic function. The resulting ventricular dysfunction may be related to a release of tumour necrosis factor-a, which may decrease myocyte shortening and mitochondrial dysfunction [75]. CAR T-cell therapy can be used to achieve remission before allogeneic stem cell transplant; therefore, the reversibility of end-organ toxicities is very important [68].…”
Section: Anti-cd19 Car T-cells Cause B-cell Aplasia and Hypogammaglobmentioning
confidence: 99%